2014
DOI: 10.1088/0004-637x/795/1/2
|View full text |Cite
|
Sign up to set email alerts
|

DISCOVERY OF A ∼5 DAY CHARACTERISTIC TIMESCALE IN THEKEPLERPOWER SPECTRUM OF Zw 229–15

Abstract: We present time series analyses of the full Kepler dataset of Zw 229−15. This Kepler light curvewith a baseline greater than three years, composed of virtually continuous, evenly sampled 30-minute measurements -is unprecedented in its quality and precision. We utilize two methods of power spectral analysis to investigate the optical variability and search for evidence of a bend frequency associated with a characteristic optical variability timescale. Each method yields similar results. The first interpolates a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
101
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 33 publications
14
101
2
Order By: Relevance
“…This work, as well as several others (Mushotzky et al 2011, Edelson et al 2014, Koz lowski 2016 have highlighted observational shortcomings in the damped random walk model of quasar variability, in which a random walk at short timescales flattens at longer timescales in the damped part. In particular, there is now rather good evidence that a non-negligible fraction of quasars exhibit variability which have significantly redder PDSs at low frequencies than expected from the random walk, with this fraction depending on the black hole mass.…”
Section: Discussionsupporting
confidence: 56%
“…This work, as well as several others (Mushotzky et al 2011, Edelson et al 2014, Koz lowski 2016 have highlighted observational shortcomings in the damped random walk model of quasar variability, in which a random walk at short timescales flattens at longer timescales in the damped part. In particular, there is now rather good evidence that a non-negligible fraction of quasars exhibit variability which have significantly redder PDSs at low frequencies than expected from the random walk, with this fraction depending on the black hole mass.…”
Section: Discussionsupporting
confidence: 56%
“…We ran simulations assuming PSD slopes of −3, −2.5, and −2 to cover most of the observed range of AGN behavior (e.g., Gonzalez-Martin & Vaughan 2012;Edelson et al 2014). Only pure power-law PSD slopes were assumed in this initial analysis; no broken or bending power laws were used.…”
Section: Ccf Significance Testingmentioning
confidence: 99%
“…Detailed modeling of quasar light curves has shown that the broadband variability is well-described to first approximation by a first-order continuous autoregressive process (i.e., a damped random walk; e.g., Kelly et al 2009Kelly et al , 2011MacLeod et al 2010), although small deviations from this behavior have been observed at short timescales using well-sampled light curves (e.g., Mushotzky et al 2011;Zu et al 2013;Edelson et al 2014;Graham et al 2014). This variable quasar continuum emission is believed to originate from their accretion disks, but the cause of Figure 2.…”
Section: Quasars In Tdssmentioning
confidence: 99%